The Immunoexpression of Glucocorticoid Receptors in Breast Carcinomas, Lactational Change, and Normal Breast Epithelium and Its Possible Role in Mammary Carcinogenesis - Raja Alyusuf; Javed Fayyaz Wazir; Urmil Prabha Brahmi; Abdul Rahman Fakhro; Moiz Bakhiet (International Journal of Breast Cancer)
The role of estrogen and progesterone receptors in breast cancer biology is well established. In contrast, other steroid hormones are less well studied. Glucocorticoids (GCs) are known to play a role in mammary development and differentiation; thus, it is of interest to attempt to delineate their immunoexpression across a spectrum of mammary epithelia. Aim. To delineate the distribution pattern of glucocorticoid receptors (GRs) in malignant versus nonmalignant epithelium with particular emphasis on lactational epithelium. Materials and Methods. Immunohistochemistry (IHC) for GRs was performed on archival formalin-fixed paraffin-embedded tissue blocks of 96 cases comprising 52 invasive carcinomas, 21 cases with lactational change, and 23 cases showing normal mammary tissue histology. Results. Results reveal an overexpression of GRs in mammary malignant epithelium as compared to both normal and lactational groups individually and combined. GR overexpression is significantly more pronounced in HER-2-negative cancers. Discussion. This is the first study to compare GR expression in human lactating epithelium versus malignant and normal epithelium. The article discusses the literature related to the pathobiology of GCs in the breast with special emphasis on breast cancer. Conclusion. The lactational epithelium did not show overexpression of GR, while GR was overexpressed in mammary NST (ductal) carcinoma, particularly HER-2-negative cancers.